Exploring Digital Supply Chain Practices in the Maritime Industry: A Systematic Literature Review - Hye, Mohammad Nazmuzzaman; Habib, Md. Mamun (ExcelingTech, 2025)
The maritime industry is undergoing a significant transformation with the integration of digital technologies to enhance efficiency, transparency, and security. This study systematically reviews the adoption of key digital technologies- such as blockchain, cloud computing, and internet of things (IoT)-with in the maritime sector. The findings reveal that digital supply chain (DSC) technologies enhance real-time data exchange, predictive analytics, and automation. Additionally, the study highlights the primary challenges hindering digital adoption, including infrastructure limitations, regulatory constraints, cybersecurity risks, and resistance to change.The contributions of this research are threefold. First, it provides comprehensive classification digital technologies in the maritime industry and their functional role in supply chain management. Second, it develops a conceptual framework that aligns digitalization Practices with performance outcomes in maritime logistics. Third, it identifies gaps in current research and proposes directions for future studies, particularly in improving interoperability, standardizing digital platforms, and assessing the long-term impact of DSC innovations. The study offers valuable insights for academics, industry practitioners, and policymakers aiming to optimize digital supply chain practices in the maritime industry.